Description of the Compliance of Women Who Experience Physical Violence in Dating - Kalisning, Wedar; Yuwono, Emmanuel Satyo (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
One type of violence that many women face is dating violence. Shock will appear when someone goes out violently. Many people are susceptible to change in response to stressful conditions. This study aims to find out how the compliance of women who experience physical violence while dating. This study used narrative qualitative methods to find these problems and analyze the picture of compliance of women who experienced dating violence. Three students of Satya Wacana Christian University, Salatiga, were involved in the study. This research data was obtained through observation and interviews. Data is analyzed by subtracting, presenting, and drawing conclusions. The results of the study found that the picture of dating violence is due to overprotective actions justified by the victim. The victim feels comfortable because the overprotective act is seen as reasonable in dating. The mechanism of obedience can then make the victim decide to continue their relationship, despite the physical violence against him.